Prevalence of cardiovascular disease risk factors among students of a tertiary institution in Ghana. Issue 2 (12th January 2018) - Ofori, Eric K.; Intiful, Freda D.; Asante, Matilda; Asare, George A.; Adjei, Patrick K.; Steele‐Dadzie, Rebecca K.; Amoako‐Mensah, Anna; Mensah, Daniel; Angmorterh, Seth K.
Abstract: Cardiovascular diseases (CVDs) are listed as one of the main causes of mortality and morbidity by the World Health Organization. The World Heart Federation lists overweight/obesity, blood lipid profile, and blood pressure as some of the modifiable risk factors to developing CVDs. This study sought to determine the prevalence of some of these modifiable risk factors among University of Ghana students. One hundred and twenty students were sampled for the study. Lipid profile parameters such as high‐density lipoprotein (HDL), total cholesterol (TC), and total triglycerides (TG) were measured using the Vitros 5‐IFS chemistry analyzer (NY, USA). The Friedewald's equation was used to determine low‐density lipoprotein (LDL) levels. Anthropometric indices such as height and weight were measured following standard protocols. Body mass index (BMI) was calculated in kg/m 2 using the height and weight measurements. The students were then categorized into underweight, normal, overweight, and obese according to their BMI. Blood pressure measurements were also taken. The mean age of the students was 30.04 ± 7.99 years. A total of 4.2%, 30%, and 67.5% had TG, TC, and LDL, respectively, above normal recommended ranges. Low HDL levels were observed in 32.5% of the students. About 45% had high systolic blood pressure and 32.5% with high diastolic blood pressure. In all, the risk factors studied contributed to about 95% of the variance in explaining the risk of developing CVDs. The study concludes that the cardiovascular risk factors assessed are prevalent among the students and therefore steps must be taken to address the increase in prevalence. Abstract : This study investigates the prevalence of the modifiable risk factors of cardiovascular diseases. The cardiovascular risk factors assessed explained 95% of the variance in the risk of developing cardiovascular diseases.